PENGARUH KETUNTASAN MOTORIK TERHADAP PEMAHAMAN SESEORANG DALAM MEMPELAJARI SERTA MENGAJAR PENDIDIKAN AGAMA ISLAM - mimi jamilah; Nilam Wahyu Syahputri (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2025)
The purpose of this scientific journal, "The Influence of Motoric Mastery on Individuals in Studying and Teaching Islamic Religious Education," is to facilitate and accelerate students' understanding and development of materials related to Islamic Religious Education, thereby facilitating the transfer of knowledge, specifically the material they have learned, and accelerating learning and teaching activities. The primary method I used in this research was literature review, compiling and analyzing data from various sources such as books, scientific articles, and journals to gather relevant information, understand theories, identify previous research, and develop a theoretical and analytical framework that supports my research topic. I then compared this with facts and my own experiences. I hope this research can help students and teachers improve their personal qualities and apply what they have learned. Keyword: Motoric Completion, Islamic Religious Education